Morphometric Characteristics Analysis of channels Network in Wadi Sassu & Wadi Tamat Basins, By Applying Geographical Information Systems (Journal of Libya for geographical studies, 2023)
This study aims at analyzing the Morphometric Characteristics For channels Network in Wadi Sassu & Wadi Tamat Basins, By Applying Geographical Information Systems (GIS) depending on Digital Elevation Models (DEM) by resolution 30*30 meter in order to determine the boundaries of the two wadies subject of the study, extract channels network, classify its grades according to Strahler (1957), determine numbers & lengths of channels in both basins, extract or derive terrain, morphometric & survey characteristics relating to channels network in both basins such as area, circumference and length of basin like basin terrain.Mathematical equations relevant to this respect were used to compute values of other numerous morphometric variables expressing the morphometric characteristics of the two basins in relation to channels network such as terrain characteristics, namely ratio of terrain, formal properties like elongation ratio, channels properties like ratio of bifurcation, river recurrence, draining density ….etc. This is in addition to study & analysis of impact of geological, natural, climatic and soil characteristics as well as the impact of morphometric, survey, terrain and formal characteristics of the two basins on morphometric properties of channels network therein, The study concluded to the study of Morphometric Characteristics For channels Network in Wadi Sassu & Wadi Tamat Basins, where extent of effect  by geological, natural, climatic and soil characteristics was evidenced and morphometric, survey, terrain and formal properties of the two basins, leading to variance in morphometric characteristics for channels network in the two basins in terms of no. of channels, lengths, drainage density, river recurrence, length of surface flow and intensity of drainage.
Keywords: Wadi Sassu Basin; Morphometric Characteristics; channels Network; Intensity of Drainage; Wadi Tamat Basin